Prenatal development of spinal cord in goats (Capra hircus) - Maya S (Department of Anatomy, College of Veterinary and Animal Sciences, 2005)
Prenatal development of the spinal cord in goat was studied using 52 foetuses of various ages, to trace the morphogenesis and histogenesis of spinal cord and its relation with developing vertebral column, foetal age and body weight. The weight, volume and length of the cord had significant correlation in between them and also with age, body weight, crown rump length, vertebral column length and other body parameters and also were more dependant on age, than on others. The maximum rate of growth was during the fifth month. The rate of growth of vertebral column and vertebral canal exceeded that of spinal cord. The maximum and minimum regional cord length were measured in the thoracic and coccygeal regions, respectively. A significant correlation existed between total cord length and length of different cord regions except coccygeal region. The lumbar enlargement contributed more to the total length than cervical enlargement at all ages. The size of spinal cord segments decreased after S1 towards the coccygeal region. The growth rate of cord regions declined in the fifth month caudal to sacral region. Up 54 days, the spinal cord extended the entire length of vertebral canal but at the fifth month, the termination was at caudal end of S2 vertebra. By 24 days, the neural tube was with ependymal, mantle and marginal layers, diamond-shaped lumen with a sulcus limitans, alar, basal, roof and floor plates and limiting membranes. The stage of the neural tube terminated by 48 days. The dorsal median sulcus and septum, ventral median fissure, dorsal intermediate groove, white matter with dorsal, ventral and lateral funiculi and gray matter with dorsal, ventral and lateral horns and a ventral commissure were seen. By fourth month, the basic structure corresponded to the adult structure. The maximum values for width and height were at the enlargements. The total width of cord was greater than the height at all levels studied. The percentage of gray matter width decreased after third month indicating a comparative increase in the growth of lateral funiculus. Vertical gray matter percentage decreased earlier indicating early growth of ventral funiculus. The multipolar neurons first appeared in the ventral horn, by 40 days. The cells had clear boundaries by fourth month. Among neuroglia, the ependyma presented a stratified layer around the central canal from the beginning of gestation. The astrocytes and oligodendrocytes appeared by 40 days. Oligodendrocytes formed myelin sheath towards the end of gestation. Microglia appeared by fourth month. In the gray matter, the ventral horns were wider in the enlargements. The lateral horn appeared by middle of the second month at thoracic, anterior lumbar and middle sacral levels. The lamina I appeared by third month. Lamina II was organised into form towards the end of third month. Lamina III appeared by the end of third month and by fifth month entered into substantia gelatinosa. Lamina IV was poorly defined even by the fifth month, and presented nucleus proprius. Lamina V appeared by 48 days with nucleus reticularis and extended the entire length of the spinal cord. Lamina VI was a broad layer by fourth month. Lamina VII presented intermediolateral and intermediomedial nuclei, cervical nucleus of Stilling and Clark’s column. The lamina VIII and IX formed the ventral horn. By 48 days, nuclear aggregations appeared and were well defined by fourth month. Medial nuclear groups were seen in all regions and lateral groups only at enlargements. In the white matter fibre tracts developed from 48 days. The white matter increased towards the end of gestation. The central canal varied in cross-section from diamond-shape to oval by 102 days. The sacral and coccygeal regions presented a terminal ventricle. The lumen contained a granular material from 40 days. Cilia appeared by 48 days and were absent towards the end of gestation, except at sacral and caudal levels. The cervical region had well developed reticular formation, cervical nucleus of Stilling, spinal accessory nucleus and phrenic nerve nucleus. The cervical enlargement had the maximum segment height. From C8 onwards, intermediolateral nucleus, reticular formation, Clark’s column were seen by middle of second month. Thoracic region presented Clark’s column, lateral horn, reticular formation, nucleus proprius and conical substantia gelatinosa. Lumbar region presented a rounded Clark’s column, elongated substantia gelatinosa, larger neurons in lamina I, nucleus proprius and reticular formation. Lateral horn disappeared at L2 and reappeared at L4 segment. The dorsal funiculus was undivided from this level onwards. Lumbar enlargement had maximum gray matter height percentage, dorsal and ventral horn width and distance from central canal to left gray matter margin. The ventral horn height percentage exceeded that of dorsal horn. More cells were seen in lamina I. Larger substantia gelatinosa, nucleus proprius, reticular formation, intermediomedial nucleus, well developed Clark’s column and nuclear aggregations were seen. The sacral region had larger dorsal horn and substantia gelatinosa, ventrally located lumen, sacral nucleus of Stilling by fourth month at S1 segment. S2 segment was with nucleus proprius, lateral horn, reticular formation and fused dorsal horns. From S4 segment, nuclear aggregations dispersed and white matter was decreased. The anterior coccygeal segments were similar to the caudal sacral segments. Conus was similar to the neural tube. The ganglia were with indistinct cell boundaries upto 48 days, later the unipolar neurons and satellite cells became distinguishable. Capsule appeared from 40 days. Pia mater, dura mater and arachnoid were differentiated by 24, 40 and 48 days of gestation respectively. A dentate ligament was seen as projections of pia mater upto S4 segment. Epidural fat appeared by the end of gestation. The luminal content and ependymal cells stained positive with PAS and Best’s Carmine. Neurons, neuroglia, neuropile and meninges were also positive for Best’s Carmine. Proteins appeared as Nissl bodies by 102 days. The lipids appeared by third month. Alkaline phosphatase was noticed in blood vessels, nucleoli of neurons and glia, neuropile, white matter, ependyma and limiting membranes. Acid phosphatase was localized in the neuroglial nuclei and ganglionic neurons.